BOGIES FOR HIGHER SPEEDS HAVING A SHORT WHEEL BASE - Orlova, A.; Kik, W.; Scheffel, H. (Science and Transport Progress, 2004)
The reduce drive time it is necessary to increase the speed of trains. Modern high speed trains have the 3-metre bogie base and an even smaller one. The base size influences significantly not only the system movement stability but the bogie frame weight as well. The base size reduction is possible with the use of the active suspension system and with the use of inter axle link construction as well.